Higher Serum 25-Hydroxyvitamin D and Lower Plasma Glucose Are Associated with Larger Gray Matter Volume but Not with White Matter or Total Brain Volume in Dutch Community-Dwelling Older Adults. Issue 8 (1st July 2015) - Brouwer-Brolsma, Elske M; van der Zwaluw, Nikita L; van Wijngaarden, Janneke P; Dhonukshe-Rutten, Rosalie A; in 't Veld, Paulette H; Feskens, Edith J; Smeets, Paul A; Kessels, Roy P; van de Rest, Ondine; de Groot, Lisette C
Abstract: Background: Previous studies have shown beneficial associations between 25-hydroxyvitamin D [25(OH)D] status and cognitive performance, but results are inconclusive. Studies on 25(OH)D status and brain volumetric measures may provide more insight in the potential role of vitamin D in cognitive performance. Objectives: The aims of this study were to cross-sectionally investigate the association between vitamin D status and brain tissue volumes in 217 Dutch community-dwelling older adults aged ≥65 y and to examine whether surrogate markers of glucose homeostasis act as modifiers in these associations. Methods: Serum 25(OH)D, plasma glucose, and plasma insulin were analyzed, serving as exposure measures. Estimates of total brain volume, gray matter volume, and white matter volume were obtained using MRI, serving as outcome measures. Associations of serum 25(OH)D, plasma glucose, and plasma insulin concentrations with brain tissue volumes were evaluated using multiple linear regression analyses. Potential effect modification by glucose homeostasis in the association between 25(OH)D and brain volumetric measures was examined by stratification and testing for interaction. Results: After full adjustment, higher serum 25(OH)D concentrations and lower plasma glucose concentrations were associated with larger gray matter volume, [β ± SE: 0.20 ± 0.08 mL ( P = 0.02) and −3.26 ± 1.59 mL ( P = 0.04), respectively]. There were no associations between serum 25(OH)D and plasma insulin concentrations with total brain volume and white matter volume. Furthermore, there was no evidence for a mediation or modification effect of plasma glucose on the associations between serum 25(OH)D and brain tissue volumes. Conclusion: Higher serum 25(OH)D and lower plasma glucose are associated with larger gray matter volume, but not white matter or total brain volume, in a population of Dutch adults aged ≥65 y. This trial was registered at clinicaltrials.gov as NCT00696514.